Benchmarking Cellulose Nanocrystals: From the Laboratory to Industrial Production - Reid, Michael S; Villalobos, Marco; Cranston, Emily D (Langmuir, 2017)
The renewability, biocompatibility, and mechanical properties of cellulose nanocrystals (CNCs) have made them an attractive material for numerous composite, biomedical, and rheological applications. However, for CNCs to shift from a laboratory curiosity to commercial applications, researchers must transition from CNCs extracted on the bench scale to material produced on an industrial scale. There are a number of companies currently producing kilogram to ton per day quantities of sulfuric acid-hydrolyzed CNCs as well as other nanocelluloses, as described herein. With the recent intensification of industrially produced CNCs and the variety of cellulose sources, hydrolysis methods, and purification procedures, the characterization of these materials becomes critical. This has further been justified by the past two decades of research that demonstrate that the CNC stability and behavior are highly dependent on the surface chemistry, surface charge density, and particle size. This work outlines key test methods that should be employed to characterize these properties to ensure a "known" starting material and consistent performance. Of the sulfuric acid-extracted CNCs examined, industrially produced material compared well with laboratory-made CNCs, exhibiting similar charge density, colloidal and thermal stability, crystallinity, morphology, and self-assembly behavior. In addition, it was observed that further purification of CNCs using Soxhlet extraction in ethanol had minimal impact on the nanoparticle properties and is unlikely to be necessary for many applications. Overall, the current standing of industrially produced CNCs is positive, suggesting that the evolution to commercial-scale applications will not be hindered by CNC production.